2020
DOI: 10.3390/plants9030330
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Perspectives in Population Genomics of the Common Bean

Abstract: Population genomics integrates advances in sequencing technologies, bioinformatics tools, statistical methods and software into research on evolutionary and population genetics. Its application has provided novel approaches that have significantly advanced our understanding of new and long-standing questions in evolutionary processes. This has allowed the disentangling of locus-specific effects from genome-wide effects and has shed light on the genomic basis of fitness, local adaptation and phenotypes. “-Omics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 91 publications
1
24
0
1
Order By: Relevance
“…After subdivision, independent domestication events occurred within each gene pool, making the evolutionary and domestication processes of the common bean a unique model for studies of domestication in plants [9]. The independent domestication processes of these two gene pools are characterized by partial and geographical reproductive barriers, which reflect the strong differentiation between Andean and Mesoamerican accessions in terms of their morphological, biochemical, and molecular traits [8,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After subdivision, independent domestication events occurred within each gene pool, making the evolutionary and domestication processes of the common bean a unique model for studies of domestication in plants [9]. The independent domestication processes of these two gene pools are characterized by partial and geographical reproductive barriers, which reflect the strong differentiation between Andean and Mesoamerican accessions in terms of their morphological, biochemical, and molecular traits [8,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have analyzed genetic diversity have already been carried out, mainly for morphological [26][27][28][29][30] and molecular [29,[31][32][33][34][35] data. Analysis of genetic diversity has demonstrated that there is greater diversity in the Mesoamerican gene pool compared to the Andean gene pool due to a bottleneck that occurred before domestication in the wild populations during the expansion to South America [8,9,18]. An analysis of the diversity and genetic structure of Brazilian landraces using microsatellite markers revealed intermediate genetic diversity in the genotypes in relation to their primary centers of diversity [36].…”
Section: Introductionmentioning
confidence: 99%
“…Common bean is a vital source of protein and micronutrition for hundreds of millions of people globally (Singh 1999;Gepts et al 2008). The crop was independently domesticated in Middle America and the Andes (Gepts 1988;Kwak and Gepts 2009;Bitocchi et al 2013;Ariani et al 2018;Cortinovis et al 2020), leading to the species' two major domesticated gene pools. These are additionally subdivided into several ecogeographic races, each with a long history of adaptation to speciic environmental conditions (Singh et al 1991;Beebe et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Andean genotypes are predominantly found in Colombia, Ecuador, Peru, Bolivia, Chile, and Argentina (Beebe et al., 2001; Tohme, Gonzalez, Beebe, & Duque, 1996). These two gene pools are further subdivided into races based on morphological and ecological adaptation; Mesoamerican beans are classified into four races (Mesoamerican, Durango, Jalisco, and Guatemala) and Andean beans are subdivided into three races (Nueva Granada, Peru, and Chile) (Beebe et al., 2000, 2001; Cortinovis et al., 2020; Kwak & Gepts, 2009; Singh, Gepts, & Debouck, 1991).…”
Section: Introductionmentioning
confidence: 99%